2013
DOI: 10.1105/tpc.112.106278
|View full text |Cite
|
Sign up to set email alerts
|

GLUCAN SYNTHASE-LIKE8 and STEROL METHYLTRANSFERASE2 Are Required for Ploidy Consistency of the Sexual Reproduction System inArabidopsis     

Abstract: In sexually reproducing plants, the meiocyte-producing archesporal cell lineage is maintained at the diploid state to consolidate the formation of haploid gametes. In search of molecular factors that regulate this ploidy consistency, we isolated an Arabidopsis thaliana mutant, called enlarged tetrad2 (et2), which produces tetraploid meiocytes through the stochastic occurrence of premeiotic endomitosis. Endomitotic polyploidization events were induced by alterations in cell wall formation, and similar cytokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 74 publications
0
44
0
Order By: Relevance
“…At first, sterol-deficiency (e.g., in the Arabidopsis hyd1 and hyd2/fk mutants) typically induces defects in embryonic patterning and body organization (Jang et al, 2000; Schrick et al, 2000; Souter et al, 2002), similar as in GSL8 loss-of-function plants, suggesting for defects in symplastic domain isolation and PD regulation. Additionally, recent studies by our lab and others revealed that weak sterol biosynthesis mutants (e.g., smt2 and fk-J3158 ) exhibit stomatal cell clusters and islands of excessive cell proliferation (Qian et al, 2013), similar as observed in the GSL8-defective chorus and et2 alleles (Guseman et al, 2010; De Storme et al, 2013), supporting the notion that structural sterols control symplastic connectivity, e.g., putatively through regulation of PD callose. Opposite to this hypothesis, (Qian et al, 2013) did not link the stomatal clustering phenotype to alterations in symplastic connectivity, but instead postulated that sterols most likely control stomatal patterning through regulation of stomatal cell fate asymmetry, e.g., by a yet unknown signaling pathway.…”
Section: A Putative Role For Sterols In Modulating Callose Depositionmentioning
confidence: 57%
“…At first, sterol-deficiency (e.g., in the Arabidopsis hyd1 and hyd2/fk mutants) typically induces defects in embryonic patterning and body organization (Jang et al, 2000; Schrick et al, 2000; Souter et al, 2002), similar as in GSL8 loss-of-function plants, suggesting for defects in symplastic domain isolation and PD regulation. Additionally, recent studies by our lab and others revealed that weak sterol biosynthesis mutants (e.g., smt2 and fk-J3158 ) exhibit stomatal cell clusters and islands of excessive cell proliferation (Qian et al, 2013), similar as observed in the GSL8-defective chorus and et2 alleles (Guseman et al, 2010; De Storme et al, 2013), supporting the notion that structural sterols control symplastic connectivity, e.g., putatively through regulation of PD callose. Opposite to this hypothesis, (Qian et al, 2013) did not link the stomatal clustering phenotype to alterations in symplastic connectivity, but instead postulated that sterols most likely control stomatal patterning through regulation of stomatal cell fate asymmetry, e.g., by a yet unknown signaling pathway.…”
Section: A Putative Role For Sterols In Modulating Callose Depositionmentioning
confidence: 57%
“…Until now, endomitosis in plants has been described as a result of defective cytokinesis due to aberrant spindle-or cell plate formation 38,56,57 . Our results show that chromosome missegregation by AHL15 overexpression-induced chromatin decondensation provides an alternative mechanism of endomitosis in plants, possibly acting not only during SE but also during gametogenesis or zygotic embryogenesis as infrequent environmentally-induced events that could lead to genome duplication-enabled speciation during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed root cells of tetraploid 35S::AHL15 seedlings showed a larger nucleus and a larger cell volume than diploid control plants ( Figure S7c), explaining the larger organ size observed for these plants. We used the centromere-specific HISTONE3-GFP fusion protein (CENH3-GFP) to count the number of chromosomes per cell 37,38 . Seven to eight CENH3-GFP-marked centromeric dots could be detected in root cells of wild-type Arabidopsis plants and diploid 35S:AHL15 SE-derived plants ( Figure S7d).…”
Section: Ahl15 Overexpression Induces Polyploidy During Se Initiationmentioning
confidence: 99%
“…Differentiated phloem remains symplasmic connected to neighbouring cells, but symplasmic connectivity is lost during xylem formation, guard cell differentiation, meiocyte (gamete) formation and embryogenesis. In these cell types PD connections are permanently closed via callose deposition, as seen in meiocytes (De Storme et al ., ; Tchorzewska et al ., ), or degraded (Kragler et al ., ). PD are transiently closed/opened via PD‐associated callose synthases/beta‐glucanases that increase or reduce the callose present at the PD pore neck region, respectively (Iglesias & Meins, ; Levy et al ., ; Vaten et al ., ).…”
Section: Phloem As a Conduit For Macromoleculesmentioning
confidence: 99%